Unleashing the Potential of Artificial Intelligence in Architecture And Development of the Built Environment: From Misconceptions to Productive Prospects (Global Journals of Research in Engineering, 2023)
Artificial intelligence invades our lives and professions at an ever-increasing pace and intensity Architecture the built environment and real estate have been joining the trend only timidly and belatedly The record of some of the most recent famous achievements in the field set straight the paper challenges the state-of-the-art concerning these fields debunks the idea of the truly creative potential of the technology and puts forward a sketch roadmap to a realistic - and significant - deployment of artificial intelligence in architecture and the built environment The attention turns to open-source patterns-platforms generative patterns processing generative pre-design parametric evaluation and optimization Leveraging the objectivity of assessments and streamlining workflows artificial intelligence promises to unleash true architectural creativity and leverage the productivity and efficiency of the design- and planning processes